Optimalisasi Persiapan Menyusui Dalam Kelas Ibu Untuk Meningkatkan Brastfeeding Self Efficacy Di Desa Carangsari - Purnamayanti, Ni Made Dwi; Budiani, Ni Nyoman; Novyadewi, I Gusti Agung Ayu; Astiti, Ni Komang Erny; Mahayati, Ni Made Dwi; Suarniti, Ni Wayan; Wirata, I Nyoman (Progran Studi Farmasi Universitas Mandala Waluya, 2025)
Breast milk is the best food for babies. Only 54% of babies aged 0-6 months receive exclusive breastfeeding in Carangsari Village. Failure to breastfeed occurs because mothers lack confidence in being able to breastfeed. The program aims to increase the breastfeeding self-efficacy of pregnant women through a breastfeeding preparation program integrated into the Kelas Ibu program. The community service method is advocacy and socialization to local leaders, preparation of a breastfeeding preparation program plan and implementation of the program for pregnant women. The community service was carried out in 2024 in Carangsari Village, Petang District, Badung Regency-Bali. Program evaluation was carried out by assessing breastfeeding self-efficacy before and after program implementation. The results of the community service were: 1) The breastfeeding preparation program integrated into the Kelas Ibu Program received support from the local leader and community; 2) The breastfeeding preparation program plan was realized in the form of a Breastfeeding Preparation Class Learning Plan and trained facilitators; 3) After the implementation of the breastfeeding preparation program, there was an increase in the breastfeeding self-efficacy of pregnant women. The implementation of the integrated breastfeeding preparation program in the Kelas Ibu Program can be continued to increase the success of providing exclusive breastfeeding.